Who Sets the Agenda? the Dynamic Agenda Setting of the Wildlife Issue on Social Media. Issue 3 (3rd April 2023) - Wang, Xiaohui; Chen, Liang; Shi, Jingyuan; Tang, Hongjie
ABSTRACT: Following the COVID-19's outbreak in China, wildlife-related issues such as wildlife management and conservation made headlines around the world due to the potential zoonotic nature of the newly discovered coronavirus. In our study, we examined the dynamic interaction of the news agenda and public agenda concerning wildlife-related issues on social media after COVID-19's outbreak. Using big data analytics, we automatically extracted the agendas' attributes and networks from 110, 549 social media posts made from January 1 to April 8, 2020, and investigated the effect of second- and third-level dynamic agenda setting in a time series analysis. Our findings suggest that the agenda-setting effect of wildlife-related issues on social media was not a single-step, unidirectional action but a reciprocal, dynamic interaction constantly constructed by news outlets and the general public.